The Suzuki Reaction Applied to the Synthesis of Novel Pyrrolyl and Thiophenyl Indazoles - Chiara Oliviero; Tecla Gasperi; Maria Antonietta Loreto; Antonella Migliorini (Molecules, 2012)
The paper describes the Suzuki cross-coupling of a variety of N and C-3 substituted 5-bromoindazoles with N-Boc-2-pyrrole and 2-thiopheneboronic acids. The reactions, performed in the presence of K2CO3, dimethoxyethane and Pd(dppf)Cl2 as catalyst, gave the corresponding adducts in good yields. The methodology allows the facile production of indazole-based heteroaryl compounds, a unique architectural motif that is ubiquitous in biologically active molecules.